في الطلاب الجامعيين الاصحاء aureus (MRSA) Methicillin - Resistant Staphylococcus الحمل الأنفي لمعنقوديات الذهبية المقاومة لممثيسمين - جاسم, أمنه نصيف; عبدو, هدى سهيل; عبد, شيماء عواد (Al-Nahrain Journal of Science, 2012)
The present study was conducted to determine the prevalence of Methicillin – Resistant Staphylococcus aureus (MRSA) of nasal colonization in healthy community. Two hundred nasal swabs were collected from students from Baghdad University (males and females). The isolates obtained from nasal swab cultured on selective media were identified by conventional microbiological procedures. Only 44 S. aureus strains were isolated, and the S. aureus nasal carriage percentage was 22%. The results of antibiotics susceptibility testing was performed using the disk diffusion method showed that 29 isolates of bacterium were resistance to methicillin (14.5%). Nasal carriage percentage of MRSA was in female (18%) more than it was in male (11%). MRSA isolates varied in their resistance to other antibiotics and showed high resistance to penicillin (100%), Gentamicin (93.1%). All MRSA isolates were sensitive to chloramphenicol and Rifampin.